Peran Perpustakaan dalam Meningkatkan Mutu Pendidikan di Universitas Muhammadiyah Ponorogo - Eny Supriati (IAIN Ponorogo, 2017)
Abstract: This research applied qualitative design. The result of the data of this research is collected by observation and documentation and interview. The findings showed that 1) the planning process of library services in improving the quality of education at the Muhammadiyah University of Ponorogo (Unmuh) in accordance with George R. Terry’s view, however, Muhammadiyah University of Ponorogo apply detailed process of planning consisting of five steps. The first step is determining vision, mission and goals of library which is appropriated to the vision, mission and goals of an institution. Secondly, strategic plan must be formulated. The third step is setting up library’s work programs, namely annual, semiannual and monthly work program. The fourth is developing library program comprising of the human resources, collection and facilities and infrastructure development. The final step is planning for evaluation. 2) the implementation of the library service in the Muhammadiyah University of Ponorogo support George R. Terry and Hasibuan’s viewpoint. It emphasizes for stages of implementation. The first stage is formulating quality standards and instructions as a guideline for each library staff to serve users. The second phase is distributing responsibilities, function and authority. The third is developing good relationship, coordination and communication among library staffs. The fourth stage is evaluating library service. 3) the evaluation of library services at the Muhammadiyah University of Ponorogo refers to the view of George R. Terry that comprising two categories namely internal and external evaluation. Internal evaluation relates to two straight evaluation, namely evaluation conducted by leaders to the library and vice versa. Furthermore, external evaluation concerns in the evaluation carried out by library to the users.Abstrak: Penelitian ini bertujuan untuk menjelaskan 3 (tiga) rumusan masalah yaitu; bagaimana perencanaan, pelaksanaan, dan evaluasi layanan di perpustakaan Universitas Muhammadiyah (Unmuh) Ponorogo. Penelitian ini menggunakan pendekatan kualitatif, dengan pengumpulan data melalui wawancara mendalam, studi dokumentasi, dan observasi. Hasil penelitian ini menunjukkan bahwa, 1) Perencanaan layanan di perpustakaan Universitas Muhammadiyah Ponorogo bersesuaian dengan pendapat George R. Terry. Namun, di perpustakaan Unmuh Ponorogo memberikan penjelasan lebih detail lagi menjadi lima tahapan, yaitu pertama penentuan visi, misi,dan tujuan perpustakaan yang disesuaikan dengan visi, misi, dan tujuan institusi, kedua pembuatan renstra perpustakaan, ketiga pembuatan program kerja perpustakaan, keempat pembuatan program pengembangan perpustakaan yang terdiri dari pengembangan sumber daya manusia, pengembangan kelembagaan, dan pengembangan sarana dan prasarana perpustakaan, kelima perencanaan evaluasi perpustakaan, 2) Pelaksanaan layanan di perpustakaan Universitas Muhammadiyah Ponorogo mendukung teori yang dikemukakan George R. Terry dan Hasibuan yang dijelaskan lebih rinci menjadi empat tahapan, yaitu pertama pembuatan prosedur mutu dan instruksi kerja yang digunakan sebagai pedoman dalam pelaksanaan layanan oleh masing masing staf, kedua pembagian kerja, fungsi dan wewenangnya, ketiga pembinaan hubungan kerja, koordinasi dan komunikasi yang baik, keempat kegiatan evaluasi layanan perpustakaan, 3) Evaluasi layanan di perpustakaan Universitas Muhammadiyah (Unmuh) Ponorogo juga bersesuaian dengan teori George R. Terry yang dijelaskan menjadi dua kegiatan. Pertama evaluasi internal, yang dijabarkan menjadi dua, yaitu evaluasi yang dilakukan oleh pimpinan kepada perpustakaan dan evaluasi dari perpustakaan kepada pimpinan, kedua evaluasi eksternal, yaitu evaluasi dari pihak perpustakaan kepada pemustaka.